Multiple reflections on the monarch-subject relationship of Confucianism during the Ming and Qing Dynasties - Zong, Jinbei (2024)
The Ming and Qing dynasties marked a period of great change in Chinese political and cultural thought. During this period, the monarch-subject relationship was a central theme in the study of Confucianism and a central component of traditional Chinese culture, which has long been the focus of interest among scholars in various fields. This paper examines the development of ancient Chinese monarch-subject relations from the perspective of historical factors and the development of Confucianism. In addition, the relationship of the monarch-subject relationship in Ming and Qing Confucianism is analyzed and discussed based on the influential thinkers’ theories, such as Gu Yanwu, Huang Zongxi and Wang Fuzhi. This analysis offers valuable insights into the comprehensive innovation of Confucianism in the new historical context.